(untitled) (Journal of Informatics and Mathematical Sciences, 2012)
In this paper, we have proposed the definition of a fuzzy region with holes in a general fuzzy topological space in such a way that the holes and the generalized region are disjoint with each other. In particular, the topological relations between fuzzy regions each with a single hole have been obtained.